ANALISIS KARAKTERISTIK PARKIR PADA RUMAH SAKIT UMUM DAERAH KABUPATEN BREBES - Sadewo, Wasis Aziz; Budirahardjo, Slamet; Rizani, Mohammad Debby (Universitas PGRI Semarang, 2025)
The Brebes Regional General Hospital which is located on Jalan Jenderal Sudirman No.181 Pangembon, Brebes District, Brebes Regency is one of the hospitals managed by the Brebes Regency government with class B type. There is a problem with parking at the Brebes Regional Hospital, namely there is no balance between the number of parking spaces available with the number of visitor vehicles coming due to limited parking space. Therefore, this research was carried out with the aim of knowing the characteristics of parking. The data taken in this research is primary data in the form of vehicle volume and secondary data in the form of the number of parking spaces at Brebes Regional Hospital. Based on survey and analysis results, it is known that the highest parking volume was 769 motorbikes and 191 cars. The highest parking accumulation was 461 motorbikes and 70 cars. The highest parking index value is 131.7% for motorbikes and 116.7% for cars. The highest average parking duration was for motorbikes, 54.1 minutes and cars, 54.1 minutes. The highest turnover rate for motorbikes is 0.24 vehicles/lot/hour and cars are 0.05 vehicles/lot/hour. The largest dynamic capacity for motorbikes is 3261 units and cars are 574 units.